2017
DOI: 10.2106/jbjs.16.01044
|View full text |Cite
|
Sign up to set email alerts
|

Double-Row Arthroscopic Rotator Cuff Repair Is More Cost-Effective Than Single-Row Repair

Abstract: Economic and Decision Analysis Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Cost analysis on surgical techniques in arthroscopic RCR also revealed varying results. While Genuario et al 16 reported in their analysis on the cost-effectiveness of single-row RCR versus double-row RCR that double-row RCR was not cost-effective for any sized RCTs, Huang et al 23 found double-row RCR to be more cost-effective than single-row RCR in some cases, especially in larger RCTs. This discrepancy most likely results from the varying underlying costs of surgery that were used for calculations, depending on the health care system.…”
Section: Discussionmentioning
confidence: 98%
“…Cost analysis on surgical techniques in arthroscopic RCR also revealed varying results. While Genuario et al 16 reported in their analysis on the cost-effectiveness of single-row RCR versus double-row RCR that double-row RCR was not cost-effective for any sized RCTs, Huang et al 23 found double-row RCR to be more cost-effective than single-row RCR in some cases, especially in larger RCTs. This discrepancy most likely results from the varying underlying costs of surgery that were used for calculations, depending on the health care system.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, a later cost-utility analysis by Huang et al [67], indicated that even though there were no significant differences in functional or qualityof-life measures between single row and double row repair technique, double row repair was more cost effective than SR. There was also noted that DR fixation was more economically friendly for tear larger than 3 cm.…”
Section: Costmentioning
confidence: 98%
“…The cost-effectiveness of rotator cuff repair may be affected by the relative risk of retear rates because revision surgery for retear carries an additional cost burden. 6 Bisson calculated the costs to the US healthcare system to transition from the single row to the suture bridge technique and found that large decreases in revision rates would be necessary to justify the added cost. 7 Brown et al performed a meta-analysis to evaluate suture configuration, repair method and tear size on retear rates and found that the suture technique may not affect rerupture rates after rotator cuff repair.…”
Section: Limitationsmentioning
confidence: 99%